Antifouling effects of the periostracum on algal spore settlement in the mussel Mytilus edulis. Issue 1 (December 2016) - Kang, Ji-Young; Bangoura, Issa; Cho, Ji-Young; Joo, Jin; Choi, Yoo; Hwang, Dong; Hong, Yong-Ki
Abstract In nature, marine mussels (Mytilus edulis ) suffer less fouling colonization on the newly formed sides of their shells. Using settlement assays with algal spores ofPorphyra suborbiculata, we determined that spore attachment and germination on the periostracum decreased to 36.8 and 3.3 %, respectively. Additionally, the spore settlement was considerably diminished by periostracum dichloromethane extracts containing 19 % oleamide, a major antifouling compound. A scanning electron micrograph of the surface revealed a regular ripple structure with approximately 1.4 μm between ripples. Based on these results, mussel periostraca or their associated biomimetic materials may become environmentally friendly, antifouling agents for preventing the settlement of soft foulants.